Acute effect of aerobic exercise with blood flow restriction on blood pressure and heart rate in healthy young subjects - Cirilo-Sousa, Maria do Socorro (2017)
The aim of the present study was to verify the acute effect of the aerobic exercise (AE) with blood flow restriction (BFR) upon systolic (SBP), diastolic blood pressure (DBP) and heart rate (HR) in health youngsters. Participated in the present study 13 young normotensive students (19.5 ± 1.7 years old). The sample was randomly divided into two experimental protocols: stationary race with BFR and stationary race without BFR. Subjects performed 5 sets of 2 minutes with 1 minute of rest interval for both protocols. SBP, DBP and HR were measured at rest, in the end of the exercises and during 60 minutes after conditions. The AE without BFR presented hypotensive effect 60 minutes post exercise (p= 0.029); the AE with and without BFR elevated significantly the SBP and HR immediately post exercise (p< 0.05) and the AE with BFR presented higher DBP and HR values immediately post-exercise when compared to AE without BFR (p= 0.001; p< 0.001, respectively). It is concluded that the AE without BFR does not seem to maximize the hypotensive effect, both sessions can increase SBP and HR immediately post-exercise with significant higher values in DBP and HR for AE with BFR.